2020
DOI: 10.1038/s41598-020-59518-x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet potato viromes in eight different geographical regions in Korea and two different cultivars

Abstract: The sweet potato in the family Convolvulaceae is a dicotyledonous perennial plant. Here, we conducted a comprehensive sweet potato virome study using 10 different libraries from eight regions in Korea and two different sweet potato cultivars by RNA-Sequencing. Comprehensive bioinformatics analyses revealed 10 different virus species infecting sweet potato. Moreover, we identified two novel viruses infecting sweet potato referred to as Sweet potato virus E (SPVE) in the genus Potyvirus and Sweet potato virus F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…For example, this is the first study reporting eight viruses, including PVY, ChiVMV, CMV, CaCV, PCSV, PCV-2, TNRV, and TMGMV, as well as two viroids, CLVd and PCFVd, infecting pepper in Vietnam. Furthermore, we were able to determine the proportion of individual viral pathogen in a given sample and distribution of identified viruses and viroids in different regions and plants, as shown in the previous studies [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 92%
“…For example, this is the first study reporting eight viruses, including PVY, ChiVMV, CMV, CaCV, PCSV, PCV-2, TNRV, and TMGMV, as well as two viroids, CLVd and PCFVd, infecting pepper in Vietnam. Furthermore, we were able to determine the proportion of individual viral pathogen in a given sample and distribution of identified viruses and viroids in different regions and plants, as shown in the previous studies [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 92%
“…Poly(A) RNA-based enrichment has been used for both RNA and DNA viruses, but it is not applicable for the detection of viruses without a poly(A) tail [ 33 ]. However, our several previous virome studies using RNA sequencing with mRNA libraries demonstrated that different types of viral genomes, regardless of the presence of poly(A) tail, can be identified by RNA sequencing with polyA selection [ 16 , 17 , 18 ]. In addition, currently, preparation of mRNA library is much cheaper than library deleting ribosomal RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The development of next-generation sequencing (NGS) facilitates the identification and diagnosis of plant viruses, including novel viruses [ 12 , 13 , 14 ]. In addition, NGS has been widely used for several plant virome studies [ 15 , 16 , 17 , 18 ]. However, few studies have identified viruses infecting soybean using NGS [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virome research has gradually become a hot spot in virus research and has been reported in a number of crops and fruits ( Jo et al, 2017 , 2018 , 2020 ; Pecman et al, 2017 ). Although these studies based on NGS have identified known or novel viruses, comprehensive studies associated with potato viromes have been scarce.…”
Section: Discussionmentioning
confidence: 99%